Nursing students’ experiences of developing multicultural leadership in community-based HIV/AIDS programs in Papua - Edison Kabak (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Cultural diversity in health care, particularly within HIV/AIDS programs in Papuan communities, necessitates that nursing students develop leadership skills sensitive to variations in values, beliefs, and community practices. Cultivating multicultural leadership is therefore a critical component in strengthening the professional competence of future nurses. Purpose: To examine the experiences of nursing students in developing multicultural leadership during the implementation of HIV/AIDS programs in Papuan communities. Method: A descriptive phenomenological study was conducted among 12 nursing students using purposive sampling. Data were collected through semi-structured interviews and analyzed using Colaizzi's seven-step phenomenological method. Results: Five major themes emerged: (1) multicultural awareness as the foundation of leadership; (2) adaptation processes in culturally diverse settings; (3) the role of mentors in leadership development; (4) communication challenges in community practice; and (5) the formation of culturally sensitive leadership. Field experiences were found to play a pivotal role in shaping students’ multicultural leadership competencies. Conclusion: Multicultural leadership among nursing students develops through experiential learning, reflection, and community engagement. Integrating culture-based learning into nursing curricula is essential to prepare students for the complexities of delivering health services in diverse populations.